2011
DOI: 10.1063/1.3625261
|View full text |Cite
|
Sign up to set email alerts
|

Observation of plasma density dependence of electromagnetic soliton excitation by an intense laser pulse

Abstract: Borghesi, M. (2011). Observation of plasma density dependence of electromagnetic soliton excitation by an intense laser pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…33 We note that previous studies on the EM soliton have largely concentrated on the underdense plasma close to the critical surface and have indicated that solitons are not observed if the plasma density is far below n c . 10,20,30 However, the plasma density employed in our experiments was relatively low. We know soliton generation is closely connected with the initial plasma density n e0 , because a key condition for EM field trapping is that the frequency in the rear portion of an intense laser pulse decreases to the local plasma frequency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 We note that previous studies on the EM soliton have largely concentrated on the underdense plasma close to the critical surface and have indicated that solitons are not observed if the plasma density is far below n c . 10,20,30 However, the plasma density employed in our experiments was relatively low. We know soliton generation is closely connected with the initial plasma density n e0 , because a key condition for EM field trapping is that the frequency in the rear portion of an intense laser pulse decreases to the local plasma frequency.…”
Section: Methodsmentioning
confidence: 99%
“…This is mainly because Raman scattering is neglected in deriving the formula, which attributes the frequency downshift to the energy depletion. 7,9,30 Raman scattering though is fundamental in decreasing the laser frequency and thus soliton formation. 24 In the low-density region, the cascade-to-condensate caused by SRS tends to weaken.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…Many particle in cell (PIC) simulations [41][42][43][44][45][46][47] and experimental investigations [48][49][50][51] reveal the appearance of multidimensional EM localized structures and light bullets in laser plasmas. It is believed that 44,45 nearly 25%-40% of the laser pulse energy goes into the generation of these well localized concentrations of electromagnetic energy, which can play an important role in the laser plasma interaction process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the numerical identifications of solitons, among the different kinds of coherent structures that are formed by an intense laser pulse in a plasma, stimulated a renewed interest in developing an analytical model and in envisaging ways of detecting solitons experimentally [4]. The em soliton [5] found in 1D and 2D simulations consist of slowly or nonpropagating electron density cavities inside which an em field is trapped and oscillates coherently with a frequency below the unperturbed plasma frequency and with a spatial structure corresponding to half a cycle.…”
Section: Introductionmentioning
confidence: 99%